STUDY OF TAXPAYER'S COMPLIANCE WITH TAX KNOWLEDGE AS INTERVENING VARIABLES IN THE PATAMA TAX SERVICE OFFICE (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
Taxes play a vital role in the life of the state, especially in the implementation of development. This is because taxes are the main source of state revenue to finance all costs, including development expenditures.The government seeks to obtain funding from within the country instead of foreign debt to realize national development. The government collects state revenues in order to succeed in national goals, namely through increasing sources of state revenue so as to create domestic financial independence. State revenue is included in the revenue component in government accounting. State revenue comes from non-tax state revenues (PNBP) and central taxes. The mainstay sector that plays the dominant role in providing the largest contribution to state revenue is tax revenue. The largest proportion of national income comes from taxes paid by citizens. The following research uses primary data. Sugiyono (2016) states, primary sources are sources that directly provide data to data takers. The population of this research are all taxpayers of KPP Pratama. The following study uses a sampling technique with non-probability sampling with convenience sampling. Convenience sampling is a sample selection technique based on population elements whose data is easy to obtain, namely those who are willing to be respondents as samples Keywords: Tax Services, Tax Socialization, Tax Knowledge, Taxpayer Compliance